2014
DOI: 10.3174/ajnr.a4139
|View full text |Cite
|
Sign up to set email alerts
|

Patency of the Anterior Choroidal Artery after Flow-Diversion Treatment of Internal Carotid Artery Aneurysms

Abstract: BACKGROUND AND PURPOSE:Treatment of cerebral aneurysms with flow diverters often mandates placement of the device across the ostia of major branches of the internal carotid artery. We determined the patency rates of the anterior choroidal artery after placement of flow-diversion devices across its ostium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…7,83 Our study has several merits compared with the previously published articles. First, because our study includes all available studies in this important field, it presents a complete overview of all available evidence on the adverse events in FDD strategies.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…7,83 Our study has several merits compared with the previously published articles. First, because our study includes all available studies in this important field, it presents a complete overview of all available evidence on the adverse events in FDD strategies.…”
Section: Discussionmentioning
confidence: 70%
“…44 Currently, parent vessel reconstruction with FDDs is rapidly becoming the preferred endovascular modality for giant and complex IAs. 7 In some areas, FDD application has drastically decreased the rate of coil and stent usage. …”
mentioning
confidence: 99%
“…4,21 On the other hand, smaller vessels such as the anterior choroidal and lenticulostriate arteries and perforating vessels with no distal collaterals may maintain flow due to a pressure gradient across the ostium and are more likely to remain patent. 3,18,21 The higher rate of ophthalmic artery patency after flow diversion can probably be attributed to a higher continued physiological demand with the ophthalmic than the PCoA. 6 Furthermore, because both systems have an adequate collateral circulation, clinical symptoms do not usually develop in occluded arteries and in arteries with diminished flow.…”
Section: Discussionmentioning
confidence: 98%
“…10 Finally, 2 reports with a combined total of 43 anterior choroidal arteries spanned by at least 1 FDS in the treatment of carotid aneurysms documented 2 branch occlusions (4.7%) at follow-up, without clinical sequelae. 11,12 No study found a significant association between branch occlusion and the number of FDS devices placed across vessel ostia.…”
Section: Discussionmentioning
confidence: 99%